Depression among elderly in Rumah Seri Kenangan Cheng and Rumah Seri Kenangan Seremban, 1997 - Sabariah Abd. Hamid; Hanafiah Mohd Salleh (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Depression is a common clinical syndrome in the elderly, often resulting in attempted and / or successful suicide. Studies have shown that depression prevalence were higher among the elderly in institution. Therefore the objective of this study is to know more about depression and its contributing factors among the elderly in institution. 205 respondents have been selected from Rumah Seri Kenangan Cheng and Rumah Seri Kenangan Seremban by using universal sampling for this cross sectional study. Medical records and structured questionaire have been used for collecting data. The overall prevalence for this population was 37.6% and was higher in women (50.7%) than in men (30.3 %). The prevalence also increased with age. However there were no significant relationships to depression were found in both sexes for ethinicity , marital status, education, income, health and its duration. Univariate analysis identified causes of admission were also associated with depression in which prevalence was higher among those who have been caught (58.6 %) than in voluntary admission (22.9 % ). However the duration of stay was not affect the onset of depression. Better physical environment which includes leisure and basic needs was identified as a factor contributing to the low rate of depression (24.5 % ) found in this study. Whereas social environment and services were not significantly correlated with rates of depression. So in terms of prevention by risk factor, there were factors that irreversible which includes biological factors and reversible factor such as physical environment. Improvement in such measures may be important in reducing prevalence of depression in elderly people.